Períodos do dia em exposição a doses de atividade física moderada a vigorosa e indicadores do perfil lipídico em adolescentes: um estudo longitudinal - Barbosa, Arthur Oliveira (2021)
The association of physical activity (PA) practiced in real-life conditions with lipid profile indicators in adolescents is null or inconsistent. These results may be due to the emphasis on analyzing the total volume of physical activity of moderate to vigorous intensity (MVPA), disregarding the different ways that adolescents can be exposed to the practice during the day. Thus, the objectives of this study were: a) to systematically review the literature regarding the association between indicators of physical activity and lipid profile in adolescents, and b) to analyze the association between the number of periods of the day exposed to different doses of AFMV and lipid profile indicators in adolescents. For the first objective, systematic searches were carried out in the following databases: Scopus, Web of Science, PubMed, SciELO and LILACS, in English, Spanish and Portuguese, from January 2008 to May 2021. In the second, it was performed an original study with longitudinal observational design, with four years of follow-up and three data collection points, conducted with adolescents from public schools in the city of João Pessoa, Paraiba (10 to 13 years, mean 11.6 ± 0.7, 53.5% were female, in 2014). Time in AFMV and sedentary behavior (CS) was measured by GT3X+ accelerometers (ActiGraph). The operationalization of the periods of exposure to AFMV doses was defined as follows: determination of the average daily time of AFMV for each period of the day – morning (06:00 to 11:59), afternoon (12:00 to 17:59) and night (6:00 pm to 11:59 pm); categorization of the meantime of MVPA in each period of the day in practice (Yes = 1) or not practiced (No = 0) doses of ≥5, ≥10 or ≥15 minutes; and summation of doses and recategorization in exposed to 0, 1 or ≥2 periods of the day at doses of ≥5, ≥10 or ≥15 minutes AFMV. The lipid profile indicators were: total cholesterol (TC), triglycerides (TG), high-density lipoproteins (HDL-c) and low-density lipoproteins (LDL-c), non-HDL-c, CT/HDL and TG/ HDL. The Generalized Estimating Equations model was used to analyze the association between the number of periods of the day exposed to different doses of MVPA and lipid profile indicators in adolescents, adjusted for sex, age, economic class, skin color, hours of sleep, saturated fat and fiber intake, body mass index, time in CS and baseline values of the lipid profile indicator analyzed. The systematic review results included 79 studies, 45.6% classified as having moderate methodological quality, and 87.3% were crosssectional. There was an inverse association between the number of steps and CT; positive of leisure-time PA and meeting the recommendations for PA with HDL-c in cross-sectional studies. In the longitudinals, there is a positive association between the time of AFMV and HDL-c. In the original study, there is an inverse association between greater quantity of periods of the day exposed to ≥5-minute doses of AFMV and TC, non-HDL-c and TG/HDL-c and with ≥10 and ≥15-minute doses to all indicator’s lipid profile, except for HDL-c. Concluded that more active adolescents tend to have better lipid profile values and that this benefit extends to those who practice MVPA, even if it is from short-duration doses.